Improved Mechanisms Commanditaire Vennootschap (CV) Become A Legal Entity Limited Liability Company (PT) - Yayah Wariah; Rudiana Eka Pramana Putra; Amin Purnawan (Jurnal Akta, 2018)
Principal difference between a limited partnership or known as CV (Commanditaire Vennootschap) with limited liability company (PT) contained in the legal status, because the CV is a partnership that is not incorporated and responsibilities of the board ally itself to a private property. While the Limited Liability Company (PT) is a legal entity liability company and limited responsibilities.The purpose of this study is to investigate and find out the mechanism of change Guild (CV) Become a Legal Entity Limited Liability Company (PT). To investigate and determine Responsibilities of complementary Allies Against Limited Liability Company (PT) established. The method used is normative, descriptive analysis, data collection is done by using primary data and secondary data in the form of primary legal materials, secondary and tertiary as the main data. After the secondary and primary data collected, then conducted a qualitative analysis. Based on the analysis concluded that the mechanism of the change in form of a CV to PT generally refers to the provisions regulating the CV and the provisions governing PT. Responsibility in complementary ally if the legal actions referred to in Article 12 and Article 13 of the Company Law, then the shift right and duty of the complementary allies into the company and legal actions undertaken by the complementary binding partner company.Keywords: Business Entity; Limited Partnership; Limited Liability Company